Secondary bacterial infection in dengue fever and associated risk factors - An observational study in children - Sridhurga Udayasankar; Vijayanand Sivakumar; Raja Sundaramurthy (Wolters Kluwer Medknow Publications, 2020)
Background: Dengue fever remains one of the leading causes of hospitalization among children in endemic areas. Clinical manifestations of dengue fever are highly variable. There are only a few pediatric dengue fever cases reported with secondary bacterial infection. Knowledge of prevalence, risk factors, and predictors of bacterial infection among children with dengue fever is essential to initiate antibiotics. Objective: The objective of this study was to assess the prevalence of bacterial infection, analysis of risk factors, and predictors of bacterial infection among dengue fever patients with prolonged or recurrent fever after critical phase of illness. Design: This was a retrospective observational study. Setting: This study was conducted in the pediatric department of a tertiary hospital. Patients: Children with dengue fever who present with persistent or prolonged fever even after critical phase were included in the study. Results: Eighty-three children with dengue fever who had persistent fever for more than 5 days or recurrent fever were included in our study. Twenty-nine patients (34.9%) had definite secondary bacterial infection confirmed by positive culture and seven patients had probable secondary bacterial infection. The risk of secondary bacterial infection was higher in infants (P = 0.054), children who had fever >5 days on admission (P = 0.020), and children who had severe dengue (P = 0.016). The duration of hospital stay increased significantly in those with secondary bacterial infection (P = 0.041). No mortality was reported in culture-positive group. Conclusion: Our study highlights the increased risk of multidrug-resistant secondary bacterial infection among infants and in children who presented with fever >5 days and severe dengue fever. Hence, a low threshold to work up for secondary bacterial infections and early initiation of empirical antibiotics is warranted in these patients.